Analysis of adverse drug reactions in a tertiary care emergency medicine department: prevalence, preventability and reporting - Patel, Shreya R.; Gupta, Sapna D.; Patel, Kamlesh P.; Malhotra, Supriya D.; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse drug reactions (ADRs) are negative consequences of drug therapy. ADR results in diminished quality of life, increased physician visits, hospitalizations, and even death. Hence a study was planned to detect and analyze ADR encountered in emergency medicine department. Methods: Data was collected over a period of 1 year after taking approval from IRB (Institutional Review Board) and written informed consent from patients. ADRs presenting as a cause of hospital admission or developed during hospitalization were analyzed. Results: A total of 229 ADRs were analyzed. Majority of ADRs were found in the age group of 40-60 Years. The M: F Ratio was 1.10:1. According to Wills and Brown Classification, majority of the ADRs belonged to Type A. According to Hartwig and Siegel classification of severity of ADRs, 18.78% of the ADRs were severe in nature. According to Schumock and Thornton preventability score, majority (64.19%) of the ADRs were not preventable, whereas 17.03% were definitely preventable. 120 (52.40%) of the ADRs were serious in nature Anti-infective were the most common drug class (30.13%) followed by CVS (24.03%) group of drugs. About (57.64%) ADRs fall in the category of probable/likely. Regarding their Outcome, 44.10% of the ADRs were recovered and 43.23% were recovering. Conclusions: Anti-infective were the most reported drug class to cause ADRs in a tertiary care emergency medicine department. Causality assessment according to WHO-UMC and Naranjo’s causality assessment criteria reported to be Probable. Whereas modified Schumock and Thornton scale preventability scale showed that majority were not preventable.